Problems and Challenges Involved in Using Integrated Urban Development Planning Tools. Example of a Development Strategy and Revitalisation Programmes - Boryczka, Ewa M. (Studia Ecologiae et Bioethicae, 2022)
Polish cities are changing constantly and, in the age of intense socio-economic, environmental and political transformation, they have to cope with many problems and challenges. In order to successfully solve the problems and challenges facing cities, local government units should apply integrated strategic management tools. Development processes (including revitalisation) can be directed using a range of tools. Local authorities responsible for the monitoring of development in territorial self-government units, such as cities, have at their disposal a wide range of development policy instruments and can actively shape development processes. Urban development strategies and revitalisation programmes are among the key tools of integrated management and planning used in Polish cities. They are integrated development programmes covering all aspects of city operations (social, economic, spatial-environmental, and technical). However, putting them in place faces a number of problems and challenges when they are drafted and implemented. Problems and challenges can be divided into three key groups of barriers: systemic barriers, social capital barriers, and information and communication barriers. The purpose of this article is to identify and characterize two key instruments of integrated urban development planning and management (namely, the city development strategy and revitalization program). This paper also attempts to identify the key issues and challenges involved in using tools such as the integrated development strategy and revitalisation programme in urban development management by local authorities.